SLEEP DISTURBANCES AMONG PATIENTS WITH ALZHEIMER’S DISEASE BY THE SLEEP-50 SCALE AT THE NATIONAL INSTITUTE OF MENTAL HEALTH, BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the prevalence, patterns, and related factors sleep disturbances using the Sleep-50 scale in patients with Alzheimer’s disease (AD) receiving treatment at the National Institute of Mental Health.Subjects and methods: A cross-sectional descriptive study was conducted on 103 patients diagnosed with Alzheimer’s disease according to ICD-10 criteria. Sleep disturbances were evaluated using the Sleep‑50 questionnaire, covering nine sleep‑related domains.Results: Based on the Sleep 50, sleep disturbances were identified in 78.6% of participants. The most common disorders were insomnia (86,4%), sleep apnea (22,2%), and circadian rhythm disorder (18,5%).  Among those with insomnia, difficulty maintaining sleep was the most frequent symptom (85,7%). Sleep disturbance was significantly associated with later-onset AD (OR=6,12; 95% CI: 2,22–16,89; p
Keywords: Alzheimer’s disease, sleep disorders, Sleep-50, insomnia, circadian rhythm disorder.